Design and Development of Student Attendance Management System Using Intel Atom Processor - Cherukumalli, Suresh; Sudhir Babu, A (International Journal of Computer Sciences and Engineering, 2025)
The proposed work demonstrates the automation of students identification, bio-data and attendance maintenance which is one of the important tasks in college. But in case of large number it becomes difficult and clumsy. So to automate it, RFID’s are used in this project we perform different functions like Identification of students, Attendance details with timing information. To detect the RFID tags, a software program is developed in Intel Atom Board with ARM 7Processor supporting Linux environment and Python Script along with GSM Modem and RF module detects the RFID tags. Whenever the RF tag comes into the vicinity of the RF reader, the GSM Modem sends SMS to the particular Parents. The main advantage of implementing student identification using Intel Atom Board is that the digital output can be directly connected to any P.C. and can monitor it continuously.